Editorial Foreword IJSLS Volume 3 Number 2 - Irianto, Sulistyowati (The Indonesian Journal of Socio-Legal Studies, 2024)
This edition of the journal presents three articles on environmental issues. The first article examines the impact of tourism policies in the Komodo National Park on the indigenous peoples who inhabit the region. The second article analyses the efforts of Jakarta residents to access justice for clean water, while the third article considers the water conservation efforts that have resulted in land conflicts in Manggarai, Nusa Tenggara. The remaining two articles address women's issues, specifically the representation of women in parliament and the phenomenon of electronic-based sexual violence.